Efektivitas Model Pembelajaran SSCS (Search, Solve, Create, Share) Pada Materi Sistem Pertahanan Tubuh Terhadap Hasil Belajar Siswa SMAN 2 Mempawah Hilir - Andriani, Yuni; N, Nawawi; Trisianawati, Eka (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Education is all the knowledge learned throughout life in all places and situations that have a positive influence on the growth of each individual being that education takes place throughout life. The less than optimal learning outcomes of students are caused by the lack of student activity in the learning process, which is influenced by learning methods that are less interactive and effective. Biology learning materials that have not reached the Learning Objective Achievement Criteria (KKTP) are materials on the body's defense system. One of the innovations in Education is the use of the SSCS (Search, Solve, Create, Share) learning model. The method used is the Quasi Experimental Design method with a quantitative approach. The results of the study were the average Pretest in the experimental class, namely 50.31 after the SSCS (Search, Solve, Create, Share) learning model was applied, the Posttest value increased with an average value of 86.25. For the effectiveness value, the calculation results were 72.32 where 64.00 â‰¤ E â‰¤ 100% was declared effective. Based on the data analysis that has been carried out, it can be concluded that the SSCS (Search, Solve, Create, Share) learning model can influence student learning outcomes and is effective for application in the learning process.